CAPTURING OF CARBON DI OXIDE AND PREVENTION OF CORROSION IN BIOMASS PRODUCTION - Anil Gupta; Himanshu Rajput; Dr. Manoj Gattani (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
The generation of heat, electricity is being produced through biomass burning process, but it is seen that it has many challenges. The capture and storage of CO2emissions produced from the combustion of biomass and many other industrialization processes is a great deal to the world. Carbon di oxide emission percentage is continuously increasing in the atmosphere, thus this leads to the climate change in the form of global warming. This study analyses the viable and potent method of capturing carbon di oxide, transporting it in an affordable way and finally then safe storage of itself and increase the temperature as well as corrosive resistivity.